(untitled) (INNOVATIVE ECONOMY, 2025)
Kostetskyi Ya.I., Siranchuk V.I., Shynkarchuk M.B., Yarema V.V. THE ECONOMIC ESSENCE AND FEATURES OF THE FORMATION OF THE INNOVATION AND INVESTMENT POTENTIAL OF ENTERPRISES IN A TERRITORIAL COMMUNITY Purpose. The aim of the article is to deepen theoretical approaches to defining the economic essence of the innovation and investment potential of enterprises within a territorial community and to substantiate the features of its formation under conditions of decentralization and transformational changes in the economic environment. Methodology of research. The research process employed a method of analysis and synthesis, which made it possible to examine the structural elements of the innovation and investment potential of enterprises, identify the interrelationships between innovation resources and investment opportunities, and summarize the key factors in its formation at the local community level. To clarify the theoretical provisions and deepen the understanding of the category of “innovation and investment potential” an abstract and logical method was used, which contributed to the formation of a holistic view of the economic essence of this concept and the determination of its role in ensuring the sustainable development of local entrepreneurship. To identify trends in the development of local community enterprises and determine the impact of the institutional environment on innovation and investment processes, the method of induction and deduction was used, which made it possible to move from individual facts to general conclusions. The application of a systematic approach made it possible to consider the innovation and investment potential of enterprises as a multi-component system that is formed under the influence of internal resources of enterprises and external social and economic conditions of the territorial community. Findings. The economic essence of the innovation and investment potential of enterprises in the territorial community as a complex category combining innovation activity, investment capacity, and institutional conditions for local development has been clarified. Theoretical approaches to the interpretation of innovation and investment potential have been systematized, and its key components have been identified, taking into account the territorial aspect. The main factors shaping the innovation and investment potential of enterprises within the community in the context of decentralization have been identified, in particular the role of local authorities, business infrastructure, and human capital. The relationship between the level of development of the innovation and investment potential of enterprises and the social and economic growth of the territorial community has been substantiated. Originality. Theoretical approaches to interpreting the economic essence of the innovation and investment potential of local community enterprises have been deepened by considering it as an integrated category formed under the influence of the innovative activity of enterprises, investment capacity, and institutional conditions for local development. The essence of the innovation and investment potential of enterprises in the territorial community has been substantiated, taking into account the conditions of decentralization and changes in the economic environment. Practical value. The results of the study can be used by local authorities in developing and implementing strategies for the social and economic development of local communities, programs to support entrepreneurship and innovation. The obtained theoretical generalizations and conclusions can be applied by enterprise managers to substantiate management decisions regarding the formation and effective use of innovation and investment potential, increasing the investment attractiveness and competitiveness of business. The results of the study can serve as a methodological basis for further scientific developments, as well as be used in the educational process when teaching economic and management disciplines. Key words: innovation and investment potential, territorial community, innovative development, investment activity, regional development.